Time-averaged Potential for Molecular Ions in Three-Dimensional Radio Frequency Traps - Rudyi, Semyon; Rozhdestvensky, Yuri (Journal of Applied Nonlinear Dynamics, 2026)
This study deals with distinctive features of forming an effective potential for molecular ions and diatomic structures in three-dimensional radio-frequency traps. A simple model is proposed, which demonstrates the transition from vibration dynamics of micro-motion and micro-rotation to the time-averaged pseudopotential and rotation potential. It shows the existence of equilibrium states of a dimer molecule, which determine the stable orientation of an ion within the space of a three-dimensional Paul ion trap. Stable states and orbits for symmetrical and asymmetrical configurations were found.